2016
DOI: 10.1111/jmft.12167
|View full text |Cite
|
Sign up to set email alerts
|

Training for Connection: Students' Perceptions of the Effects of the Person‐of‐the‐Therapist Training on Their Therapeutic Relationships

Abstract: The Person-of-the-Therapist Training (POTT) is a program designed to facilitate clinicians' ability to consciously and purposefully use their selves to effectively connect, assess, and intervene with clients. This study explored CFT students' perceptions of the effects of POTT on their ability to create positive therapeutic relationships. Course papers and final reflections were collected from 70 CFT students. Directed content analysis looking for evidence-supported elements of positive therapeutic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Two recent studies on POTT support the perceived effectiveness of the training (Niño, Kissil, & Cooke, ; Niño et al, ). Findings suggest that key outcomes of the training are congruent with its stated goals.…”
Section: Person‐of‐the‐therapist Trainingmentioning
confidence: 86%
“…Two recent studies on POTT support the perceived effectiveness of the training (Niño, Kissil, & Cooke, ; Niño et al, ). Findings suggest that key outcomes of the training are congruent with its stated goals.…”
Section: Person‐of‐the‐therapist Trainingmentioning
confidence: 86%
“…In relation to POTT, awareness of one's emotional processing while in the presence of clients, enhanced capacity to experience one's emotions, and better management of one's emotional responses to clients, were some of the professional gains reported by master's level students who had participated in POTT (Niño et al., ). POTT trainees described these gains in emotional processing as central to the improvement of their clinical skills because these changes allowed them to be more empathically present with their clients and be better able to regulate their emotional responses (Niño, Kissil, & Cooke, ; Niño et al., ). A study by Montagno, Svatovic, and Levenson () with clinicians who had completed a 4‐day externship training in EFT found that clinicians improved their competence in EFT, and that this improvement was associated with an enhanced ability to process their own emotions.…”
Section: Similarities Between Pott and Eftmentioning
confidence: 99%
“…The influence of post-Milan developments brought about the use of reflecting team formats in training and supervision (Neden & Burnham, 2007;Tseliou, 2010) whereas dialogic approaches to therapy seem to have inspired training in the dialogic self of the therapist (Rober, 2010). Against such a polymorphic background, the proposals for incorporating the development of reflexive awareness and reflexive skills in family therapy training extend from nonsystematic suggestions (Neden & Burnham, 2007;Tseliou, 2010) to systematic proposals of models like the development of the Person Of the Therapist Training program (POTT) (Aponte & Kissil, 2014;Niño, Kissil, & Cooke, 2016).…”
Section: Reflexivity In Systemic Family Therapy and Trainingmentioning
confidence: 99%